Inducible plasmid-determined resistance to arsenate, arsenite, and antimony (III) in escherichia coli and Staphylococcus aureus. - Silver, S (1981)
Plasmids in both Escherichia coli and Staphylococcus aureus contain an "operon" that confers resistance to arsenate, arsenite, and antimony(III) salts. The systems were always inducible. All three salts, arsenate, arsenite, and antimony(III), were inducers. Mutants and a cloned deoxyribonucleic acid fragment from plasmid pI258 in S. aureus have lost arsenate resistance but retained resistances to arsenite and antimony, demonstrating that separate genes are involved. Arsenate-resistant arsenite-sensitive S. aureus plasmid mutants were also isolated. In E. coli, plasmid-determined arsenate resistance and reduced uptake were additive to that found with chromosomal arsenate resistance mutants. Arsenate resistance was due to reduced uptake of arsenate by the induced plasmid-containing cells. Under conditions of high arsenate, when some uptake could be demonstrated with the induced resistant cells, the arsenate was rapidly lost by the cells in the absence of extracellular phosphate. Sensitive cells retained arsenate under these conditions. When phosphate was added, phosphate-arsenate exchange occurred. High phosphate in the growth medium protected cells from arsenate, but not from arsenite or antimony(III) toxicity. We do not know the mechanisms of arsenite or antimony resistance. However, arsenite was not oxidized to less toxic arsenate. Since cell-free medium "conditioned" by prior growth to induced resistant cells with toxic levels of arsenite or antimony(III) retained the ability to inhibit the growth of sensitive cells, the mechanism of arsenite and antimony resistance does not involve conversion of AsO2- or SbO+ to less toxic forms or binding by soluble thiols excreted by resistant cells.